Feminism a graphic guide - Jenainati, Cathia (Icon Books Ltd, 2019)
"What is feminism? Why are we still talking about it, and what can it tell us about ourselves, our societies and prejudices? In this unique, illustrated introduction, we'll explore the early history of the conscious struggle against sexist oppression, through the modern "waves" of feminism, up to present-day conversations about MeToo, intersectional feminism, and women's rights in the Middle East. We'll look at critical theory, popular action and the social and cultural forces that affect attitudes toward gender, women's lives and the struggle for equality. And we'll hear about the contributions of pioneers like Mary Wollstonecraft, Simone de Beauvoir and Kimberlé Crenshaw. As we'll see, feminism is at once global, local and individual. Written by Cathia Jenainati with illustrations from Judy Groves and Jem Milton, 'Feminism: a graphic guide' engages with the heated debates taking place in our homes, workplaces and public spaces - and the work still to be done."--Back cover